(untitled) (Conferencea, 2024)
Alisher Navoi, as an Uzbek poet and thinker in the 15th century, made a great contribution to the development of philosophical ideas and teachings on the perfection of man. His work deeply explored the concepts of man about himself, his spiritual and moral development, and the concept of the "perfect man". The main topics that occupy a special place in Navoi’s philosophical views are issues such as intellectual and spiritual growth of man, self-organization and self-improvement. His work demonstrates the desire to create an image of a perfect man. This study is devoted to the study of Navoi’s philosophical worldview, his views in the fields of epistemology, ontology and moral philosophy.